2017
DOI: 10.1016/j.ijwd.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy in female pattern hair loss

Abstract: Female pattern hair loss is the most common cause of hair loss in women and one of the most common problems seen by dermatologists. This hair loss is a nonscarring alopecia in which loss occurs on the vertex scalp, generally sparing the frontal hairline. Hair loss can have significant psychosocial effects on patients, and treatment can be long and difficult. The influence of hormones on the pathogenesis of female pattern hair loss is not entirely known. The purpose of this paper is to review physiology and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
0
43
0
1
Order By: Relevance
“…Recall, StAR has been demonstrated to play an important role in the production of steroid hormones by the transfer of cholesterol from the outer mitochondrial membrane to the inner membrane in steroidogenic tissue sites . Estrogen biosynthesis is important because it prolongs the anagen phase of the hair follicle during pregnancy and in case studies of patients with a genetic predisposition to pattern hair loss or during menopause …”
Section: Steroidogenesis (Aromatase and 5α‐reductase) Expression And mentioning
confidence: 99%
See 1 more Smart Citation
“…Recall, StAR has been demonstrated to play an important role in the production of steroid hormones by the transfer of cholesterol from the outer mitochondrial membrane to the inner membrane in steroidogenic tissue sites . Estrogen biosynthesis is important because it prolongs the anagen phase of the hair follicle during pregnancy and in case studies of patients with a genetic predisposition to pattern hair loss or during menopause …”
Section: Steroidogenesis (Aromatase and 5α‐reductase) Expression And mentioning
confidence: 99%
“…43 Estrogen biosynthesis is important because it prolongs the anagen phase of the hair follicle during pregnancy and in case studies of patients with a genetic predisposition to pattern hair loss or during menopause. 15,[44][45][46][47] In regard to pregnancy, this represents a state of hypercortisol, where this major stress hormone increases up to fourfold that has been described as a high-stress physiological state (60 μg/ mL-morning, and 20 μg/mL-afternoon). 48 Hair cortisol has been reported as a novel biomarker of hypothalamic-pituitary-adrenocortical activity, since it is incorporated into the hair shaft and studies have suggested that cortisol inhibits hair growth.…”
Section: S Teroidog Ene S Is ( Aromata S E and 5 α-Reduc Ta S E) E mentioning
confidence: 99%
“…In one survey, 40% of women experienced marital problems and 64% had career difficulties that they ascribed to their hair loss. 5 Alopecia can also be the first symptom of underlying systemic illness within the primary care setting. 1,6 FPHL is a non-scarring alopecia characterised by progressive transformation of thick, pigmented terminal hair into short, thin, non-pigmented villous hair.…”
mentioning
confidence: 99%
“…This undesired process is known as hair follicle miniaturisation. 1,3,5,6 The trigger for miniaturisation remains unclear but is postulated to be a combination of genetic predisposition, androgen influence and other not yet elucidated factors. Androgens exert their effect on hair via circulating levels of testosterone, which is produced in females by the ovaries and adrenal glands.…”
mentioning
confidence: 99%
See 1 more Smart Citation